2011
DOI: 10.1177/0020764011409523
|View full text |Cite
|
Sign up to set email alerts
|

Migrant pathways to community mental health centres in Italy

Abstract: Pathways to CMHCs are complex and influenced by many factors. Non-medical pathways to care seem to be frequent among migrants in Italy. More attention should be paid to developing psychiatric consultation liaison models that also encompass the social services and voluntary organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…This result could be partly expected considering the diferences of patients' ages. It also supports previous research performed in our country [49]. No signiicant diferences were found between migrants and native Italians in relation to living accommodation, marital status and educational level.…”
Section: Sociodemographic Featuressupporting
confidence: 92%
See 1 more Smart Citation
“…This result could be partly expected considering the diferences of patients' ages. It also supports previous research performed in our country [49]. No signiicant diferences were found between migrants and native Italians in relation to living accommodation, marital status and educational level.…”
Section: Sociodemographic Featuressupporting
confidence: 92%
“…First, these may depend on the fact that migrants may access psychiatric services when their mental distress is severe, requiring urgent and coercive measures [36,48]. Second, migrants' patern of access to psychiatric consultation in the ED may also be explained by the fact that in Italy, urgent care in this seting is ofered also to irregular/undocumented migrants, who are not allowed to atend the services of general practitioners (GPs) [49].…”
Section: Features Of Ed Referralmentioning
confidence: 99%
“…The migratory flow has mainly headed in the last decade to the Northern Italian regions, among which Emilia-Romagna region was one of the most open to newcomers that currently total 11.9% of the population (http://statistica.regione.emilia-romagna.it/servizi-online/ statistica-self-service/popolazione/popolazione-residentestraniera, accessed 1 December_2013). Despite these significant social and demographic changes, to our knowledge only few studies have been conducted on immigrants' mental health and service utilisation, some of which in Bologna (Tarricone et al 2009(Tarricone et al , 2011(Tarricone et al , 2012a(Tarricone et al , 2012bSpigonardo et al in press). In particular, differences in service use between Italians and immigrants have not been extensively investigated, with few exceptions (Gaddini et al 2008;Piazza et al 2010;Tarsitani et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that access to mental health care for migrants can be particularly difficult, notwithstanding the high psychiatric morbidity that exists in this population [24-26]. …”
Section: Introductionmentioning
confidence: 99%